2021
DOI: 10.48550/arxiv.2108.03116
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TS4Net: Two-Stage Sample Selective Strategy for Rotating Object Detection

Abstract: Rotating object detection has wide applications in aerial photographs, remote sensing images, UAVs, etc. At present, most of the rotating object detection datasets focus on the field of remote sensing, and these images are usually shot in high-altitude scenes. However, image datasets captured at low-altitude areas also should be concerned, such as drone-based datasets. So we present a low-altitude dronebased dataset, named UAV-ROD, aiming to promote the research and development in rotating object detection and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…R 3 Det is a single-stage method that has an advantage in detection speed. TS4Net [22] used a two-stage anchor refinement module that could convert the horizontal anchor boxes into high-quality oriented anchor boxes in the RetinaNet algorithm. DAL [23] and CFC-Net [2] dynamically selected high-quality anchor boxes to alleviate the divergence between classification and regression.…”
Section: A Anchor-based Detectorsmentioning
confidence: 99%
“…R 3 Det is a single-stage method that has an advantage in detection speed. TS4Net [22] used a two-stage anchor refinement module that could convert the horizontal anchor boxes into high-quality oriented anchor boxes in the RetinaNet algorithm. DAL [23] and CFC-Net [2] dynamically selected high-quality anchor boxes to alleviate the divergence between classification and regression.…”
Section: A Anchor-based Detectorsmentioning
confidence: 99%
“…We conducted comparative experiments using the UAV-ROD [15] and VisDrone2019 datasets [16]. Our comparative analysis demonstrated that our proposed method significantly outperforms existing detection models and current mainstream parameter models.…”
mentioning
confidence: 99%